2018
DOI: 10.1152/ajpregu.00423.2017
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic projections into an interconnected forebrain network control the sensitivity of male rats to diet-induced obesity

Abstract: Hindbrain catecholamine neurons convey gut-derived metabolic signals to an interconnected neuronal network in the hypothalamus and adjacent forebrain. These neurons are critical for short-term glycemic control, glucocorticoid and glucoprivic feeding responses, and glucagon-like peptide 1 (GLP-1) signaling. Here we investigate whether these pathways also contribute to long-term energy homeostasis by controlling obesogenic sensitivity to a high-fat/high-sucrose choice (HFSC) diet. We ablated hindbrain-originatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Similarly, although VMH glucose concentrations fall after insulin-induced hypoglycemia (432,446), direct injections of 2DG into the VMH are not followed by eating (464). These results, taken together with the fact that catecholaminergic neurons do not innervate the main body of the VMH (456,463), point to a coordinating rather than primary initiating role for the VMH in energy balance control.…”
Section: Which Regions Are Responsible For Initiating Eating Responses To Altered Glycemia or Glucosementioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, although VMH glucose concentrations fall after insulin-induced hypoglycemia (432,446), direct injections of 2DG into the VMH are not followed by eating (464). These results, taken together with the fact that catecholaminergic neurons do not innervate the main body of the VMH (456,463), point to a coordinating rather than primary initiating role for the VMH in energy balance control.…”
Section: Which Regions Are Responsible For Initiating Eating Responses To Altered Glycemia or Glucosementioning
confidence: 95%
“…This information arrives in the hypothalamus by way of a large contingent of ascending projections, most prominently from catecholaminergic neurons in the ventrolateral medulla and NTS (287,(456)(457)(458)(459)(460)(461). These projections innervate forebrain cell groups that make up a core network for integrating medulla-to-hypothalamus conveyed information (see Section V E 4) (456,458,462), including the long-term maintenance of glucose metabolism (463).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Rats in which hindbrain CA projections to the hypothalamus are retrogradely lesioned using the CA-selective immunotoxin, anti-DBH-saporin (31,56), increase visceral adiposity, insulin resistance, and blood glucose. These changes occur even when rats are maintained on a chow diet (16), but they are accentuated by high-fat diet. On the basis of the present findings, these effects may be attributable to destruction or malfunction of CA neurons in both the dorsal and ventral medulla, emphasizing the importance of CA neuron interaction, not only on emergency control of food intake, but also on the overall control of metabolic homeostasis and body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting phenomenon, well documented by Levin and colleagues, has shown that HFD-fed male Sprague-Dawley rats separate into two populations, one that become hyperphagic and obese, and another that maintain their eating patterns and resist weight gain [ 133 ]. Of note, hindbrain catecholaminergic ventrolateral medulla and NTS neurons that relay GI-sensitive inputs to the PVN, DMH, and ARC within the hypothalamus are disrupted in the obesity-prone population, highlighting neurodevelopmental differences that may underlie the propensity to develop DIO [ 134 ].…”
Section: Pathophysiologymentioning
confidence: 99%